Review Of The Effect Of The Family Environment And Learning Media On The Learning Process Of Children In Slum Areas - Marylin Susanti Junias (Universitas Nusa Cendana, 2022)
Abstract. Family is the first place for a child to get an education. The success of a child depends on the role of the family in providing attention and a comprehensive and mutually sustainable learning environment. In addition, optimizing a child's education is to provide children's learning media that is interesting and creative, so that learning takes place effectively. Especially for elementary school children who live in slum areas. The specific conditions and situations in the slum areas have a psychological effect on them in understanding the lesson. One of the places that help children to learn creatively and interestingly in Kupang City is the Alak Shelter House, which is a learning room for children in the slum area of ​​Alak Kupang's final waste disposal site (TPA). Different methods and uses of creative media provide a touch of psychological dynamics of its own so that children can be more open in expressing their opinions. This article reviews the current literature on the topics reviewed above. Keywords: Family Environment, Learning Media, Psychological Dynamics of Elementary School Children Abstrak. Keluarga merupakan tempat pertama seorang anak mendapatkan pendidikan. Keberhasilan seorang anak tergantung pada peran keluarga dalam memberikan perhatian dan lingkungan pembelajaran yang komprehensif serta saling berkesinambungan. Selain itu, dalam mengoptimalkan pendidikan seorang anak adalah dengan menyediakan media pembelajaran anak yang menarik dan kreatif, agar pembelajaran yang berlangsung dapat berjalan efektif. Terutama bagi anak sekolah dasar yang tinggal di daerah kumuh. Kondisi dan situasi spesifik pada daerah kumuh, memberikan pengaruh psikologis tersendiri bagi mereka dalam memahami pelajarannya. Salah satu tempat yang membantu anak untuk belajar dengan kreatif dan menarik di Kota Kupang adalah Rumah Singgah Alak, yang menjadi ruang belajar bagi anak-anak di kawasan kumuh tempat pembuangan akhir sampah (TPA) Alak Kupang. Metode dan penggunaan media kreatif yang berbeda, memberikan sentuhan dinamika psikologis tersendiri sehingga anak-anak dapat lebih terbuka dalam mengemukakan pendapatnya. Artikel ini meninjau literatur terkini tentang topik yang telah diulas di atas. Kata Kunci: Lingkungan Keluarga, Media Pembelajaran, Dinamika Psikologis Anak Sekolah Dasar